RGB free colorimeter for sensing and sorting of pigmented spheres (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The present work shows the design, development and testing of a first prototype system for classifying color pigmented spherical objects. The objective is the analysis of efficiency and error that digital photoelectric devices can have. Based on the detection of color patterns called RGB model (Red, Green & Blue) the system is composed of a digital color detector sensor TCS3472 controlled by an open source electronic platform Arduino. The ATMega328P microcontroller processes the data obtained by the sensor, which then executes the actions responsible for moving the servomotor that controls the selector mechanism which, in turn, consists of an access and output channel to three containers. An external control panel with four push buttons: start, pause, reset and emergency; the latter configured for the total disconnection of the system in case of possible jamming failures. Finally, the system delivers the results of the sphere separation by color on the control panel and physically in the repositories of the structure.